The effect of using waste newspaper in surface layers on physical and mechanical properties of three-layer particleboard - vahid vaziri; majid salari; hedayatallah Aminian; laya Jamalirad (Iranian Journal of Wood and Paper Industries, 2017)
In this study, physical and mechanical properties of particleboard made from recycled newspaper in the surface layers were investigated. Coarse and fine wood chips and recycled newspaper with dimension of 0.5 × 4 cm2 were used. The variable in this research were the ratio of recycled newspaper to wood chips (at five levels; 0:100, 15:85, 30:70, 45:55, 60:40). Urea formaldehyde resin used at 10% content on dry weight basis of the wood particles and newspaper and ammonium chloride was used as a catalyst to 2% of the dry weight of adhesive. Physical and mechanical properties of panels measured according to EN Standard. The results showed that panels containing recycled newspapers at the level of 45% had the highest bending strength and modulus of elasticity. Internal bonding and screw holding strength decreased with increasing of recycled newspaper and control sample had the highest strength. Water absorption and thickness swelling increased with increasing of recycled newspaper portion. On the basis of results of this study can be concluded that particleboard containing recycled newspapers in the surface layers up to the level of 30% can be used for general purpose boards and interior fitments (including furniture) for use in dry conditions.